1985
DOI: 10.1152/ajpregu.1985.249.6.r781
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of vasoconstrictor responses to atriopeptin II in conscious SHR

Abstract: Previous studies have demonstrated that infusion of synthetic atriopeptin II (AP II) lowered arterial pressure, reduced regional blood flow, and increased total peripheral and regional vascular resistances in conscious spontaneously hypertensive rats (SHR). This study was designed to examine the mechanism(s) involved in regional vasoconstrictor responses to AP II. In these experiments, hemodynamic actions of AP II were examined in control, 6-hydroxydopamine-treated (chemically sympathectomized), and renal-dene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…Although infusion of the peptide at each dose for longer periods might have produced somewhat greater responses, infusion of the atrial peptides for 30 minutes 33 or longer (unpublished data) in conscious SHR caused quantitatively similar changes in the hemodynamic parameters as we observed during the 15-minute infusion period. Thus, even though the infusion periods for each dose of ANF were short (15 minutes), other studies from our laboratory indicate that the infusion periods are of ample duration to accurately illustrate the hemodynamic effects of ANF under steady state conditions.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Although infusion of the peptide at each dose for longer periods might have produced somewhat greater responses, infusion of the atrial peptides for 30 minutes 33 or longer (unpublished data) in conscious SHR caused quantitatively similar changes in the hemodynamic parameters as we observed during the 15-minute infusion period. Thus, even though the infusion periods for each dose of ANF were short (15 minutes), other studies from our laboratory indicate that the infusion periods are of ample duration to accurately illustrate the hemodynamic effects of ANF under steady state conditions.…”
Section: Discussionsupporting
confidence: 72%
“…15 The increase in regional vascular resistance appears to be mediated through increased sympathetic vasoconstrictor tone, rather than through direct vasoconstrictor actions of the peptide. 33 In these studies, surgical denervation or chemical sympathectomy abolished the regional vasoconstrictor responses to ANF infusion in conscious SHR. Even in sympathectomized rats, however, sustained renal vasodilator responses were not observed during the infusion of ANF.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In summary, the present study demonstrates that ANF exerts direct vasodilator action on the fetal and neonatal renal vasculature and suggests that the decrease in renal blood flow previously observed during systemic infusion of ANF (3) was probably secondary to changes in systemic hemodynamics (22,25) and activation of compensatory mechanisms (18,19). Finally, it is shown that the renal vasodilatory response to intrarenal ANF infusion is similar in fetal and newborn sheep.…”
Section: Discussionsupporting
confidence: 71%
“…However, the present results suggest that ANF does not exert a direct vasoconstrictor action on the fetal and neonatal renal vasculature and that the site of administration of the peptide as well as the duration of the infusion play an important role in the renal hemodynamic response to ANF, as previously suggested in adults (17); systemic infusion of the peptide produces a renal vasoconstriction (3), whereas intrarenal bolus infusion produces renal vasodilation. One may speculate that systemic infusion of ANF increases sympathetic tone, which opposes the renal vasodilatory action of ANF (18,19), whereas ANF infused intrarenally is cleared rapidly by the kidney (20) and has little or no effect on sympathetic vasoconstrictor tone. In support of this hypothesis Lappe et al (1 8) have demonstrated that surgical denervation or chemical sympathectomy abolishes the renal vasoconstrictor response associated with systemic ANF infusion in spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%